Modelling the Biological Beamline at HIMAC using Geant4. (January 2019) - Bolst, D; Tran, L T; Guatelli, S; Matsufuji, N; Rosenfeld, A B
Abstract: A Geant4 simulation modelling the passive Biological beamline at the Heavy Ion Medical Accelerator Chiba (HIMAC) is described and validated against experimental measurements for a mono-energetic and spread out Bragg peak (SOBP) 12 C beam. Comparisons to experimental data showed good agreement for both lateral and depth dose profiles. It was found that simplifying the simulation model by generating a cone beam instead of using the wobbler magnets provided a good approximation for both lateral and depth dose measurements.